Ultra-low pressure drop membrane-based heat sink with 1000 W/cm2 cooling capacity and 100% exit vapor quality. (November 2020) - Alipanah, Morteza; Moghaddam, Saeed
Highlights: The most recent progress on advancing the membrane-based heat sink (MHS) science is presented. The new heat sink membrane is 7 times more permeable than the previous generation. A CHF of about 1000 W/cm 2 is achieved on a surface with A r  = 3.45 at 4 kPa pressure drop. The new membrane enhanced the heat transfer coefficient at low operating pressures. CHF versus the pumping power is 1–2 orders of magnitude higher than the other heat sinks. Abstract: This paper presents the most recent progress on advancing the membrane-based heat sink (MHS) science. A model developed to predict the MHS performance suggested that the membrane permeability limited the critical heat flux (CHF). The new generation MHS discussed here benefits from a newly developed membrane with 7 times higher permeability compared to the membrane used in the previous generation MHS. Experimental studies were conducted on a heat sink with a heater surface area of 0.7 × 0.7 cm 2 . The results confirmed that a higher membrane permeability substantially increases the CHF of surface structures with enhanced wickability and surface area ratio ( A r ) at low pressure drops. A maximum CHF of about 1000 W/cm 2 was achieved on a surface with A r  = 3.45 at a supplied liquid pressure of only 4 kPa, 2.5 times higher than the CHF reached with the low permeability membrane used in the first generation MHS. The new membrane enhanced the heat transfer coefficient at low supplied liquid pressures but substantially less than the 1.8 MW/m 2  K reached at the highest pressure (i.e. 20 kPa). This low pressure drop along with a heat sink exit vapor quality of 100% resulted in an extremely low pumping power. The ratio of CHF versus the theoretical pumping power is 1–2 orders of magnitude higher than that of the other two-phase heat sinks reported in the literature.